Active learning using a smartphone app: analysing land use patterns in Cork City, Ireland. Issue 1 (2nd January 2021) - Holloway, Paul; Kenna, Therese; Linehan, Denis; O'Connor, Ray; Bradley, Helen; O'Mahony, Bernadette; Pinkham, Robyn
ABSTRACT: Opportunities to deploy digital technologies to research agendas and active learning in tertiary education are becoming more widespread. Despite this, many research techniques are still taught using traditional "pen-and-paper" methodologies. In this article, we report on a strategy for integrating mobile technology into our large (275+) module GG1015 Applied Geography, via the use of smartphones and the ESRI Collector for ArcGIS app. Focus groups identified three common themes among students in response to using this mobile technology in geographic research. Our findings suggest that digital technologies can enhance active learning in geography for all students. Similarly, such activities should not only be reserved for small groups, and can be up-scaled for larger class sizes, particularly when using new technologies. Finally, we illustrate how the use of technology in a group setting can foster teamwork, peer-to-peer learning, and positively reinforce the uptake of digital technology in geographic fieldwork.